The Rational Design of a Financially Viable Microbial Electrolysis Cell for Domestic Wastewater Treatment - Aiken, Daniel C.; Curtis, Thomas P.; Heidrich, Elizabeth S. (Frontiers in Chemical Engineering, 2022)
Microbial electrolysis cells (MECs) are yet to achieve commercial viability. Organic removal rates (ORR) and capital costs dictate an MEC’s financial competitiveness against activated sludge treatments. We used numerical methods to investigate the impact of acetate concentration and the distance between opposing anodes’ surfaces (anode interstices width) on MEC cost-performance. Numerical predictions were calibrated against laboratory observations using an evolutionary algorithm. Anode interstices’ width had a non-linear impact on ORR and therefore allowable cost. MECs could be financially competitive if anode interstices widths are carefully controlled (2.5mm), material costs kept low ( £5-10/m2-anode), and wastewater pre-treated, using hydrolysis to achieve acetate concentrations >100mg-COD/l.